A simple approach for modeling shapes and objects with irregular boundaries and cavities by combining and interpolating parametrically defined contours - Arokiasamy, A. (Int Assoc Engineers-Iaeng, 2008)
Modeling shapes of surfaces and objects with irregular boundaries is not so easy as it will not follow any direct mathematics. So, an attempt is made to model surfaces and objects by combining contours that are defined parametrically. The method proposed here leads to the generation of objects and surfaces without specifying control points. This approach also eliminates need for inputting any data. The interpolation is done between two contours that are parametrically defined. The boundary of the surface can be changed from one contour to the other. By controlling the normal to the surface some interesting objects can also be modeled.
World Congress on Engineering 2008 -- JUL 02-04, 2008 -- Imperial Coll London, London, ENGLAND
Keywords: cavity; contour; linear interpolation; non-linear interpolation; surface modeling